Prevalence of Metabolic Syndrome and Its Parameters and Their Correlations With Psoriasis Duration, Severity, and Sleep Quality In Psoriasis Patients: A Cross-Sectional Study - Betul Tas; Vasfiye Kabeloglu (Mattioli1885, 2021)
Background: Psoriasis is an inflammatory skin disease that may lead to comorbidities, including metabolic syndrome (MS). Objective: We determined the prevalence of MS and its correlation with psoriasis duration, severity, and sleep quality in psoriasis patients. Methods: A total of 112 subjects with chronic plaque psoriasis were studied. Demographics, MS parameters, disease duration, severity, and sleep quality were examined. The Psoriasis Area and Severity Index (PASI)and the Pittsburgh Sleep Quality Index (PSQI) were used to assess psoriasis severity and sleep quality, respectively. Presence of MS and its correlations with psoriasis duration, severity and sleep quality were investigated. Results: Of 112 patients, 76 (67.8%) were diagnosed with MS. Of all patients, 74.1% had a high PASI, and 84.8% had a high PSQI. The mean values of psoriasis duration, body mass index, waist circumference, fasting glucose, HOMA-IR, triglyceride levels, blood pressure, PSQI, sleep latency, and daytime sleep dysfunction were significantly higher in the MS group than non-MS group, whereas the mean HDL level was lower. The prevalences of MS, high fasting glucose, and low HDL were significantly higher among female, but not male, patients with severe psoriasis (PASI >10) than those without severe psoriasis. Disease duration, high body mass index, waist circumference, blood pressure, fasting glucose, HOMA-IR, triglyceride levels, low HDL, and poor sleep quality were significantly correlated with the presence of MS. However, only waist circumference, fasting glucose, blood pressure, and low HDL were predictive of the development of MS. Conclusions: MS is common among psoriasis patients, and especially in females with advanced psoriasis, high fasting glucose, and low HDL levels. Besides diagnostic criteria of MS, a long duration of psoriasis, poor sleep quality and high-HOMA-IR correlate with the development of MS. High fasting glucose and low HDL levels may facilitate MS development in association with psoriasis severity in females.